Vitamin D Receptor Gene Polymorphisms and Haplotypes in Hungarian Patients with Idiopathic Inflammatory Myopathy. (14th January 2015) - Bodoki, Levente; Chen, Ji-Qing; Zeher, Margit; Nagy-Vincze, Melinda; Griger, Zoltán; Zilahi, Erika; Dankó, Katalin
Abstract : Idiopathic inflammatory myopathies are autoimmune diseases characterized by symmetrical proximal muscle weakness. Our aim was to identify a correlation between VDR polymorphisms or haplotypes and myositis. We studied VDR-BsmI, VDR-ApaI, VDR-TaqI, and VDR-FokI polymorphisms and haplotypes in 89 Hungarian poly-/dermatomyositis patients (69 females) and 93 controls (52 females). We did not obtain any significant differences for VDR-FokI, BsmI, ApaI, and TaqI genotypes and allele frequencies between patients with myositis and healthy individuals. There was no association of VDR polymorphisms with clinical manifestations and laboratory profiles in myositis patients. Men with myositis had a significantly different distribution of BB, Bb, and bb genotypes than female patients, control male individuals, and the entire control group. Distribution of TT, Tt, and tt genotypes was significantly different in males than in females in patient group. According to four-marker haplotype prevalence, frequencies of sixteen possible haplotypes showed significant differences between patient and control groups. The three most frequent haplotypes in patients were the fbAt, FBaT, and fbAT . Our findings may reveal that there is a significant association: Bb and Tt genotypes can be associated with myositis in the Hungarian population we studied. We underline the importance of our result in the estimated prevalence of four-marker haplotypes.